Can the London 2012 Olympics 'inspire a generation' To do more physical or sporting activities?: An Overview of systematic reviews - Mahtani, K.; Protheroe, J.; Slight, S.; Demarzo, M.; Blakeman, T.; Barton, C.; Brijnath, Bianca; Roberts, N. (BM J Group, 2013)
Objective: To examine if there is an increased participation in physical or sporting activities following an Olympic or Paralympic games. Design: Overview of systematic reviews. Methods: We searched the Medline, Embase, Cochrane, DARE, SportDISCUS and Web of Knowledge databases. In addition, we searched for 'grey literature' in Google, Google scholar and on the International Olympic Committee websites. We restricted our search to those reviews published in English. We used the AMSTAR tool to assess the methodological quality of those systematic reviews included. Primary and secondary outcome measures: The primary outcome was evidence for an increased participation in physical or sporting activities. Secondary outcomes included public perceptions of sport during and after an Olympic games, barriers to increased sports participation and any other nonsporting health benefits. Results: Our systematic search revealed 844 citations, of which only two matched our inclusion criteria. The quality of these two reviews was assessed by three independent reviewers as 'good' using the AMSTAR tool for quality appraisal. Both reviews reported little evidence of an increased uptake of sporting activity following an Olympic Games event. Other effects on health, for example, changes in hospital admissions, suicide rates and drug use, were cited although there was insufficient evidence to see an overall effect. Conclusion: There is a paucity of evidence to support the notion that hosting an Olympic games leads to an increased participation in physical or sporting activities for host countries. We also found little evidence to suggest other health benefits. We conclude that the true success of these and future games should be evaluated by high-quality, evidence-based studies that have been commissioned before, during and following the completion of the event. Only then can the true success and legacy of the games be established.